2014
DOI: 10.1242/jcs.144816
|View full text |Cite|
|
Sign up to set email alerts
|

iASPP is a novel autophagy inhibitor in keratinocytes

Abstract: BSTRACTThe protein iASPP (encoded by PPP1R13L) is an evolutionarily conserved p53 inhibitor, the expression of which is often upregulated in human cancers. We have recently shown that iASPP is a crucial regulator of epidermal homeostasis. Here, we report that iASPP also acts as autophagy inhibitor in keratinocytes. Our data show that depletion of iASPP protects keratinocytes from apoptosis by modulating the expression of Noxa (also known as PMAIP1). In our model, iASPP expression can affect the fissionfusion c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
41
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 96 publications
3
41
1
Order By: Relevance
“…These proteins have been described to take part in a broad range of processes related to autophagy, such as immunity (NFKBIA/IκBα, 51 IRF1 [interferon regulatory factor 1], 52,53 PPP1R13L/iASPP, 54 EIF2AK2/PKR, 55 RELA/NF-κB-p65 56,57 ) or oncogenesis (BRCA1, 58,59 MYC, 60,61 RB1 [retinoblastoma 1], 62,63 TSC2/Tuberin, 64 FOXO1, 65 XIAP 66,67 ). A few posttranslational modification enzymes have also been identified, such as 2 ubiquitin ligases (HERC1 68,69 and XIAP 66,67 ), 4 kinases (PKD2/polycystin 2, 70,71 MARK4, 72 SIK2, 73 CAMKK2/CaMKKβ 74 ), one deacetylase (HDAC4 75 ), one methyltransferase (EHMT2/G9a 76,77 ) and one phosphatase (PTPN13/PTPL1 78 ) (Table S3).…”
Section: Resultsmentioning
confidence: 99%
“…These proteins have been described to take part in a broad range of processes related to autophagy, such as immunity (NFKBIA/IκBα, 51 IRF1 [interferon regulatory factor 1], 52,53 PPP1R13L/iASPP, 54 EIF2AK2/PKR, 55 RELA/NF-κB-p65 56,57 ) or oncogenesis (BRCA1, 58,59 MYC, 60,61 RB1 [retinoblastoma 1], 62,63 TSC2/Tuberin, 64 FOXO1, 65 XIAP 66,67 ). A few posttranslational modification enzymes have also been identified, such as 2 ubiquitin ligases (HERC1 68,69 and XIAP 66,67 ), 4 kinases (PKD2/polycystin 2, 70,71 MARK4, 72 SIK2, 73 CAMKK2/CaMKKβ 74 ), one deacetylase (HDAC4 75 ), one methyltransferase (EHMT2/G9a 76,77 ) and one phosphatase (PTPN13/PTPL1 78 ) (Table S3).…”
Section: Resultsmentioning
confidence: 99%
“…438 However when the cells are much larger than those included in 439 this study such as keratinocyte cell lines in other published studies 440 were LysoTracker signals do match LC3B up-regulation [39]. 441 The technique of organelle mass quantification to determine 442 levels of mitophagy and ER elongation or phagy is a useful tech-443 nique in that it demonstrates that the same reagents can give dif- …”
mentioning
confidence: 87%
“…Blotting can be used to quantitate the degree of autophagy by mea-121 suring the autophagy marker protein, LC3B [10][11][12]. LC3B can also LC3B levels detected in this study [39]. phase of the cell cycle (Fig.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, the ATG7-deleted keratinocytes irradiated by UVA showed defective clearance of p62 and the elevation of nuclear factor-like 2 (Nrf2) target gene expression [51]. Besides the canonical autophagy pathway, ATG5/ATG7-independent but Beclin1-dependent autophagy has been described in keratinocytes [52]. These studies suggested that the canonical and non-canonical autophagy pathways in keratinocytes participate in UVR-induced autophagy.…”
Section: The Possible Role Of the Inflammasome And Autophagy In Uvmentioning
confidence: 99%